The frontier within essays by Abe Kobo - Abe, Kōbō 1924-1993 (Columbia Univ. Press, 2013)
Abe Kobo (1924-1993) was one of Japan's greatest postwar writers, recognized widely for his science fiction and plays of the absurd. He also wrote keen theoretical criticism for which he is lesser known, merging literary, historical, and philosophical perspectives. From the nature of creativity to the evolution of the human species, Abe tackled contemporary social issues and literary theory with the depth and facility of a visionary thinker
Description based upon print version of record
"Poetry and poets -- "Theory and practice in literature" -- "The hand of a calculator with the heart of a beast: what is literature?" -- "Discovering America" -- "Does the visual image destroy the walls of language?" -- "Artistic revolution: theory of the art movement" -- "Possibilities for education today: on the essence of human existence" -- "Beyond the neighbor" -- "The military look" -- "Passport of heresy" -- "The frontier within."
Keywords: Abe, Kōbō -- 1924-1993; Japanese literature; Essay; Anthologie